2001
DOI: 10.1080/00029157.2001.10403468
|View full text |Cite
|
Sign up to set email alerts
|

EEG P300 Event-Related Markers of Hypnosis

Abstract: Barabasz, Barabasz, Jensen, Calvin, Trevisan, and Warner (1999) showed that, when subjects are stringently selected for hypnotizability and responses are time locked to events, robust markers of hypnotic responding emerge that reflect alterations in consciousness that correspond to subjects' subjective experiences of perceptual alteration. To further test the Barabasz et al. (1999) hypothesis, we obtained EEG visual P300 event-related potentials (ERPs) from 20 high- and low-hypnotizable subjects. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The observed difference in ERP amplitude response between obstructive (reduced amplitude) and negative (enhanced amplitude) hallucinations (Barabasz et al, 1999;Jensen et al, 2001) is quite consistent with a searchlight or focusing model involving the anterior attention system and the anterior cingulate gyrus in particular. Breaching of a negative hallucination instruction would tend to trigger vigilance-something unexpected is happening that tends to break with the paradigm-and would likely activate the posterior attentional NEGATIVE AND POSITIVE VISUAL HYPNOTIC HALLUCINATIONS 135 system.…”
Section: Hypnotic Attention Versus Vigilancesupporting
confidence: 76%
See 1 more Smart Citation
“…The observed difference in ERP amplitude response between obstructive (reduced amplitude) and negative (enhanced amplitude) hallucinations (Barabasz et al, 1999;Jensen et al, 2001) is quite consistent with a searchlight or focusing model involving the anterior attention system and the anterior cingulate gyrus in particular. Breaching of a negative hallucination instruction would tend to trigger vigilance-something unexpected is happening that tends to break with the paradigm-and would likely activate the posterior attentional NEGATIVE AND POSITIVE VISUAL HYPNOTIC HALLUCINATIONS 135 system.…”
Section: Hypnotic Attention Versus Vigilancesupporting
confidence: 76%
“…Subjects who may have reduced their perception but not eliminated it completely might well have been surprised by the odor, and surprise increases P300 amplitude (Baribeau-Braun, Picton, & Gosselin, 1983). Barabasz accepted this interpretation (Spiegel & Barabasz, 1988) and went on to demonstrate in an elegantly designed experiment that an obstructive hallucination results in reduced ERP amplitude, whereas a negative hallucination results in increased amplitude (Barabasz et al, 1999;Jensen, Barabasz, Barabasz, & Warner, 2001). A crucial difference in the two instructions is the hardiness of the paradigm in the case of obstructive hallucination and the need to break with the paradigm if it does not work completely in the case of negative hallucination.…”
Section: Event-related Potential Studiesmentioning
confidence: 92%
“…Earlier results already indicated that amplitudes of later ERP components are reduced after the suggestion of a visual blockade 8, 17, 18 . Our study shows that this reduction is significant for a big sample consisting of low, middle and highly suggestible participants and thus conceptually replicates these observations.…”
Section: Discussionmentioning
confidence: 87%
“…For example, brain imaging and sensing methods suggest that some phenomena occur only after a hypnotic induction but not when the same subjects are using mental imagery (e.g. Kosslyn et al, 2000;Jensen et al, 2001). Thus there seems to be a puzzling little gap which needs to be explained unless we argue that the subjects did not actually try their best during the imagery condition because of either a 'hold-back' effect 14 (Zamansky, Scharf and Brightbill, 1964) or compliance (Wagstaff, 1981;.…”
Section: The Physiological Indicators Of Ascmentioning
confidence: 96%
“…Recent studies (e.g. Barabasz, Barabasz, Jensen et al, 1999;Jensen, Barabasz, Barabasz and Warner, 2001) have found changes, however, in P300 ERPs in association with a hypnotic induction, but not in a nonhypnotic imagination condition nor in low susceptible subjects. Barabasz, Barabasz, Jensen et al (1999) have further pointed out how different kinds of suggestions may lead to different results when measuring ERPs in association with hallucinations.…”
mentioning
confidence: 91%